Rhodnius spp. are differentiated based on the peptide/protein profile by matrix-assisted laser desorption/ionization mass spectrometry and chemometric tools - dos Santos Souza, Éder [UNESP]; Fernandes, Richard Perosa [UNESP]; Guedes, Wesley Nascimento [UNESP]; dos Santos, Fábio Neves; Eberlin, Marcos Nogueira; Lopes, Norberto Peporine; Padovani, Victor Damasceno [UNESP]; da Rosa, João Aristeu [UNESP] (Springer Nature, 2020)
Triatominae are hematophagous insects involved in the transmission of Chagas disease. Among the 19 genera of the subfamily, those with the highest epidemiological importance regarding the dissemination of Trypanosoma cruzi are Panstrongylus, Rhodnius, and Triatoma. Of these three genera, Rhodnius presents the greatest difficulties for specific identification. Thus, there is a need to overcome the difficulties in identifying phenotypes of similar species of this genus. In the present study, the MALDI-TOF MS methodology was used to identify 12 Rhodnius species, among the 21 admitted. The MALDI-TOF MS methodology allowed specific characterization through the identification of peptides and proteins, starting from four different methods of extraction: (A) acetonitrile/formic acid (ACN/AF), (B) acetonitrile/trifluoroacetic acid (ACN/TFA), (C) isopropyl/formic acid (IPA/AF), and (D) methanol/formic acid (MeOH/AF), and four types of MALDI-TOF matrices: α-cyano-4-hydroxycinnamic acid (CHCA), sinapic acid (SA), 6-aza-2-thiothymine (ATT), and 2,6-dihydroxyacetophenone (DHAP). The experiments were performed by combining the four solvents and four matrices to select the best MALDI extraction/matrix. The application of the MALDI-TOF MS technique, through the digital mass spectrometry approach combined with chemometric tools, such as partial least squares-discriminant analysis (PLS-DA), was able to discriminate 12 species of Rhodnius genus, which are difficult to identify using morphological characteristics. Thus, in view of the results obtained, the methodology described in the present article can be applied with speed and efficiency for the discrimination of Triatominae species. [Figure not available: see fulltext.]
Keywords: Chemometric tools; MALDI-TOF MS; Mass spectrometry; Rhodnius; Triatominae